Future scenarios of the copper industry. A prospective study of the sector in Peru - Arévalo Rodríguez, Santiago (2023)
Mining has led to multiple social conflicts between communities and companies. However, at the same time, it has been the activity with the greatest contribution to Peru’s gross domestic product for more than a decade, especially copper mining. The importance of copper lies in the fact that it is one of the basic raw materials for the manufacture of products and the expansion of global industries. This research seeks to identify and analyze the possible behavioral scenarios that will support copper mining in the next five years. Foresight (projection of future scenarios), along with the judgment of experts in the field, was used for conducting the research. This methodology employs a non-experimental design and aims at both exploratory and descriptive results. The main findings include an increase in the electricity cost for mining and the continuation of an unfavorable political leadership for its development. It is clear that this issue is taking place in a sensitive context due to the constant social conflicts that occur in favor of the growth of industry. This study will undoubtedly propose solutions to this disparity and will research whether, in any scenario, copper mining and the total population of a copper-rich country can really coexist.